An investigation of ISO/IEC 27001 adoption in South Africa - Coetzer, Christo (Rhodes University, Faculty of Science, Department of Computer Science, 2015)
The research objective of this study is to investigate the low adoption of the ISO/IEC 27001 standard in South African organisations. This study does not differentiate between the ISO/IEC 27001:2005 and ISO/IEC 27001:2013 versions, as the focus is on adoption of the ISO/IEC 27001 standard. A survey-based research design was selected as the data collection method. The research instruments used in this study include a web-based questionnaire and in-person interviews with the participants. Based on the findings of this research, the organisations that participated in this study have an understanding of the ISO/IEC 27001 standard; however, fewer than a quarter of these have fully adopted the ISO/IEC 27001 standard. Furthermore, the main business objectives for organisations that have adopted the ISO/IEC 27001 standard were to ensure legal and regulatory compliance, and to fulfil client requirements. An Information Security Management System management guide based on the ISO/IEC 27001 Plan-Do-Check-Act model is developed to help organisations interested in the standard move towards ISO/IEC 27001 compliance.
Keywords: ISO 27001 Standard; Information technology -- Security measures; Computer security; Data protection